An Analysis of Student Errors in Solving Higher Order Thinking Skills Problems on Number Patterns Using Newman's Theory - Shiddieqy, Ahmad Fauzi Ash; Kartini; Maimunah (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
In an era where Artificial Intelligence is reshaping various sectors, education must evolve to equip students with the skills required to tackle complex future challenges. Mathematics, as a fundamental subject, plays a crucial role in fostering Higher Order Thinking Skills (HOTS), which are essential for problem-solving in diverse real-world contexts. This study investigates student errors in solving HOTS problems on number patterns at SMPN 23 Pekanbaru, utilizing Newman's Error Analysis framework. A qualitative descriptive approach was employed, with data collected through written tests and interviews. The study involved 26 students from class VIII D during the second semester of the 2023/2024 academic year. Data analysis was conducted inductively, classifying errors according to Newman's stages. The findings revealed that the most frequent errors occurred during the comprehension stage (69%) and encoding stage (54%), largely due to students' inadequate understanding of number pattern concepts and limited exposure to varied HOTS problems in the classroom. These results highlight the need for a broader range of HOTS problems in mathematics education to better develop students' higher-order thinking abilities. The study recommends that educators diversify problem types, offer guided problem-solving activities, and engage in action research to refine teaching methods and enhance student outcomes.